2007
DOI: 10.1007/s10562-006-9005-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcination procedure on the catalytic property of sulfated zirconia

Abstract: Calcination parameters, such as atmosphere, duration and catalyst bed depth have a marked influence on the catalytic and spectroscopic properties of sulfated zirconia. Sulfated zirconia calcined in nitrogen or synthetic airflow, in deep bed, exhibited comparable activity in n-butane isomerization at 373 K, which suggests that oxygen is not necessary for formation of active sites. Catalysts calcined in shallow bed are catalytically inactive. Thus, the bed depth is concluded to be crucial for the formation of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…5 Other authors also indicated the importance of labile sulfate groups for activity. 22 Contrary to some zirconia samples, sulfated by a procedure similar to that applied in this work, in which the amount of incorporated sulfates were directly proportional to the surface area of the SZ, 20 all the samples investigated in this study had the same amount of sulfates, i.e., 4.2 mass %, Table II. 7 In addition, the procedure of the calcination step seems to be important.…”
Section: Resultsmentioning
confidence: 81%
“…5 Other authors also indicated the importance of labile sulfate groups for activity. 22 Contrary to some zirconia samples, sulfated by a procedure similar to that applied in this work, in which the amount of incorporated sulfates were directly proportional to the surface area of the SZ, 20 all the samples investigated in this study had the same amount of sulfates, i.e., 4.2 mass %, Table II. 7 In addition, the procedure of the calcination step seems to be important.…”
Section: Resultsmentioning
confidence: 81%
“…This promoting effect of nonspecific olefins addition indicated that the alkene may be one of the intermediates in alkane isomerization because of its higher reactivity to form carbenium ion species than alkane . Nevertheless, SZ‐based material still exhibited isomerization activity after removing all alkenes in the raw, implying the in situ generation of olefins on the SZ surface. At this point, the alternative oxidative dehydrogenation (ODH) activation of alkane on SZ surface was proposed and evidenced.…”
Section: Activation Of Alkane Over Sulfated Zirconiamentioning
confidence: 99%
“…This implied a strong chemical interaction between sulfate species and amorphous zirconia was formed during the calcination, which facilitated the formation of tetragonal zirconia and highly active sites. Indeed, the calcination protocol strongly affected the n ‐alkane isomerization activity . Chen et al suggested that the formation of active sites involved a two‐step surface reaction between sulfate species and superficial hydroxyl groups of zirconium hydroxide: Zr0.25emOH4n+xH2SO4Zr0.25emOH4n2xSO4x+2xH2normalO Zr0.25emOH4n2xSO4xZrO2nnormalx0.25emSO4x+()2nnormalxH2normalO …”
Section: Determination Of Intrinsic Structure‐reactivity Relationshipmentioning
confidence: 99%
“…Pyrosulfates are generally considered to be the most important species for activation and conversion of n-butane, [44] therefore DRIFTS was employed to investigate the sulfate structure. Figure 3 shows the DRIFT spectra obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these species seem to be minority species which initiate the reaction at high conversion levels for Cat_SZ1, whereas no activity was observed for Cat_SZ2. The initial step of the reaction cycle was proposed, by Li et al, [44] to be a stoichiometric redox reaction. The assumption of a minority species being responsible for initializing the isomerization reaction was also established by Breitkopf et al [47] by selective poisoning of surface centers.…”
Section: Resultsmentioning
confidence: 99%